2018
DOI: 10.1186/s41182-018-0101-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, temporal, and spatiotemporal analysis of under-five diarrhea in Southern Ethiopia

Abstract: BackgroundDespite improvements in prevention efforts, childhood diarrhea remains a public health concern. However, there may be substantial variation influenced by place, time, and season. Description of diarrheal clusters in time and space and understanding seasonal patterns can improve surveillance and management. The present study investigated the spatial and seasonal distribution and purely spatial, purely temporal, and space-time clusters of childhood diarrhea in Southern Ethiopia.MethodsThe study was a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 44 publications
4
21
0
2
Order By: Relevance
“…In addition to that a positively association was observed between increase of monthly average temperature and increase of diarrhea cases. Similar ndings have been elucidated in different studies [14,16,17,20,[23][24][25]. The increase cases observed during months with highest temperature justi ed by plausible explanations; higher temperature promotes the development of and growth of bacteria even though some evidences suggest that the survival and transmission of enteric viruses are increased during low temperature [26].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition to that a positively association was observed between increase of monthly average temperature and increase of diarrhea cases. Similar ndings have been elucidated in different studies [14,16,17,20,[23][24][25]. The increase cases observed during months with highest temperature justi ed by plausible explanations; higher temperature promotes the development of and growth of bacteria even though some evidences suggest that the survival and transmission of enteric viruses are increased during low temperature [26].…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies conducted in similar setting like in Rwanda contradict with the ndings [20,21] whereby they reported a decrease tendency. However another study conducted in Ethiopia found similar ndings [16]. Rwanda has made effort to decrease morbidity and mortality of diarrhoeal diseases; in the same context, much have been done to improve and strengthen the health system.…”
Section: Discussionmentioning
confidence: 66%
“…In addition to that a positively association was observed between increase of maximum temperature and increase of diarrhea cases. Similar findings have been elucidated in different studies [14,16,17,20,[23][24][25]. The increase cases observed during months with highest temperature justified by plausible explanations; higher temperature promotes the development of and growth of bacteria even though some evidences suggest that the survival and transmission of enteric viruses are increased during low temperature [26].…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies conducted in similar setting like in Rwanda contradict with the findings [20,21] whereby they reported a decrease tendency. However another study conducted in Ethiopia found similar findings [16]. Rwanda has made effort to decrease morbidity and mortality of diarrhoeal diseases; in the same context, much have been done to improve and strengthen the health system.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation